Histopathology of intestinal inflammation related to reactive arthritis. Issue 4 (April 1987) - Cuvelier, C; Barbatis, C; Mielants, H; De Vos, M; Roels, H; Veys, E
Abstract : This study has identified a group of patients with inflammatory chronic, or relapsing acute arthritis who even in the absence of gastrointestinal symptoms have histological evidence of ileocolitis. At colonoscopy simultaneous biopsies of the terminal ileum and colon were taken from 108 patients with reactive arthritis (n = 55) or ankylosing spondylitis (n = 53), 47 patients with other rheumatic diseases and 19 control patients suffering from colonic polyps, adenocarcinoma, or chronic constipation. All control patients and all but one patient with rheumatoid arthritis, juvenile chronic arthritis, systemic lupus erythematosus, lumbar back ache, and psoriatic arthritis did not have histological evidence of acute or chronic inflammatory bowel disease. In contrast, in 30 of 35 (56.6%) patients with ankylosing spondylitis, and in 37 of 55 (67%) patients with reactive arthritis, regardless of HLA B27 phenotype, there was histological evidence of inflammatory bowel disease with features either of acute enterocolitis, or early Crohn's disease. Only 18 of 67 (27%) of the patients with histological gut inflammation, however, had intestinal symptoms.